Amoxicillin dosing and pharmacokinetics in obesity for the treatment of bacterial respiratory infection secondary to COVID-19: a systematic review (Research, Society and Development, 2022)
Objective: To conduct a systematic review of Amoxicillin (AMX) dosing and pharmacokinetics (PK) in obese subjects for the treatment of the outpatient respiratory tract infection which may be a secondary co-infection with COVID-19. Methodology: A systematic review was performed up to January 2022 on MEDLINE, EMBASE, and Web of Science. Full-text manuscripts describing AMX dosing for respiratory infection or PK in obese children, adults, and RYGB bariatric patients treated with AMX were included. Results: A total of 179 records were screened, of which 8 met the inclusion criteria. Four studies described AMX dosing in obese children and adults, while 4 described PK in obese adults and RYGB bariatric subjects. Overall, in the dosing studies, 54% of children >20 kg and 10%